Off the Beaten Track—A Hitchhiker's Guide to Beryllium Chemistry. Issue 36 (1st July 2016) - Naglav, Dominik; Buchner, Magnus R.; Bendt, Georg; Kraus, Florian; Schulz, Stephan
Abstract: This Minireview aims to give an introduction to beryllium chemistry for all less‐experienced scientists in this field of research. Up to date information on the toxicity of beryllium and its compounds are reviewed and several basic and necessary guidelines for a safe and proper handling in modern chemical research laboratories are presented. Interesting phenomenological observations are described that are related directly to the uniqueness of this element, which are also put into historical context. Herein we combine the contributions and experiences of many scientist that work passionately in this field. We want to encourage fellow scientists to reconcile the long‐standing reservations about beryllium and its compounds and motivate intense research on this spurned element. Who on earth should be able to deal with beryllium and its compounds if not chemists? Abstract : Be prepared : This Minireview presents an introduction to beryllium chemistry. Its toxicity, and that of its compounds, is put into perspective, and safe handling practices are presented. Observations demonstrating the unique chemistry of beryllium and its industrial use are shown and future challenges identified. The picture shows Be metal under Ar in a glass ampule. Picture: A. Heddergott.